Auctions in Photovoltaic Solar Energy Plants And Grid Parity in Peru - Arredondo, James (2020)
In the present work an analysis is made of the network parity situation between conventional electric energy sources for the case of Peru, which would come from hydroelectric and thermoelectric energy, with renewable energy resources or simply renewable energies in this case is analyzed the photovoltaic solar energy installed between Moquegua, Tacna and Arequipa. It is seen how the rates paid by the end user of residential type are calculated, as well as the current rates provided by the corresponding agencies. Subsequently, we see the evolution of photovoltaic solar energy and the four auctions that took place in Peru, and how these costs have been decreasing significantly. Finally it is seen that in the end the goal of achieving network parity is achieved.